As estratégias de reprodução na agricultura familiar em Turvo (SC) - Minatto, João Marcos (2003)
The aim of this work is to analyze the transformations occurred in the agrarian sphere of Turvo after the expansion of the capitalist relations of production, focusing on the strategies of family reproduction. Turvo is in the south of Santa Catarina, and its economy is based on farming and cattle raising, explored in small properties owned by families, which also provide the main workmanship. Along with the modernization in agriculture, the productive base has changed and specialized agricultural activities were developed to attend the market – in this irrigated rice (as the main product), tobacco plant, chicken and swine can be highlighted. Moreover, the producers adopt various strategies to reproduce themselves. The tendencies indicate a revitalization of the diversification of the farming and cattle raising activities, as much as to attend the market, as to auto-sustainability.